Adolescent dental arch development among Southern Chinese in Hong Kong: a geometric morphometric approach - Wen, Yi Feng (Sci Rep, 2019)
This study aimed to investigate changes in types of dental arch form during adolescence and explore adolescent changes in size and form of dental arch. Hong Kong Chinese were recruited and digital dental arch models were obtained at ages 12, 15, and 18 years. Geometric morphometrics was used to investigate adolescent changes of dental arch form. There were 225 participants from whom digital models at all three age periods were available. Three types of dental arch form were identified through clustering. Significant changes (p < 0.001) in types of dental arch form were noted during age 12–18 years. During age 12–18 years, significant changes in centroid size and form of dental arch were observed (p < 0.001). No significant changes were observed during 15–18 years. Adolescent changes of dental arch form occur primarily during age 12–15 years, whereas dental arch form was relatively stable during age 15–18 years.